Seleção e associação genômica para precocidade sexual em bovinos da raça Nelore - Irano, Natalia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to perform genome-wide association to detect chromosomal regions associated with indicator traits of sexual precocity of Nellore cattle, and evaluating methodologies for prediction of genomic values to use for selection of these traits. Data from Nellore animals belonging to farms integrating animal breeding programs of DeltaGen® and Paint® (CRV Lagoa), were used. Age at first calving (AFC), the occurrence of early pregnancy of heifers (EP) and scrotal circumference (SC) were used as traits associated with sexual precocity. After quality control and consistency of phenotypic data, information of 68,170; 72,675 and 83,911 animals with phenotype, and of 1,738; 1,770 and 1,680 genotypes for AFC, EP and SC, respectively, and 412,993 SNPs, remained for analysis. In chapter 2, the estimates of the SNP effects were obtained using the single-step method (WssGBLUP). All animals were used applying single trait animal model to predict the genetic values and, subsequently, the solutions of the SNP effects were obtained from these genetic values. The 10 windows of 150 SNPs that captured the greatest proportion of variance explained by markers were identified. The 10 windows with greater effect obtained for EP are located on chromosomes 5, 6, 7, 14, 18, 21 and 27 and together explained 7.91% of the total genetic variance. For SC, these windows are on chromosomes 4, 8, 11, 13, 14, 19, 22 and 23, explaining 6.78% of the total variance. With GWAS analysis it was possible to identify chromosomal regions associated with EP and SC. Identifying these regions enables better understanding and evaluation of these traits, besides indicating candidate genes for future research studies of causal mutations. In Chapter 3, two multi-step methods were used to estimate the marker effects - GBLUP and IBLASSO; besides the single-step method (ssGBLUP). Observed phenotype was used as the dependent variable to estimate the genomic value ...

Objetivou-se com este estudo realizar associação genômica ampla, visando detectar regiões cromossômicas associadas a características indicadoras de precocidade sexual de bovinos da raça Nelore, bem como avaliar metodologias para a predição de valores genômicos visando à seleção destas características. Foram utilizados dados de animais da raça Nelore, pertencentes a fazendas que integram os programas de melhoramento genético da DeltaGen® e Paint® (CRV Lagoa). As características associadas à precocidade sexual utilizadas neste estudo foram a idade ao primeiro parto (IPP), a ocorrência de prenhez precoce de novilhas (P16) e o perímetro escrotal (PE). Após o controle de qualidade e consistência dos dados fenotípicos, permaneceram para as análises informações de 68.170, 72.675 e 83.911 animais com fenótipo e de 1.738, 1.770 e 1.680 animais genotipados para IPP, P16 e PE, respectivamente, e 412.993 SNPs. No Capítulo 2, as estimativas dos efeitos dos SNPs foram obtidas utilizando-se a metodologia single-step (WssGBLUP). Todos os animais foram utilizados aplicando-se modelo animal unicaracterística para predizer os valores genéticos e, posteriormente, as soluções dos efeitos dos SNPs foram obtidas a partir destes valores genéticos. Foram identificadas as 10 janelas de 150 SNPs que capturaram a maior proporção da variância explicada pelos marcadores. As 10 janelas de maior efeito obtidas para a P16 estão localizadas nos cromossomos 5, 6, 7, 14, 18, 21 e 27 e somadas explicaram 7,91% da variância genética total. Para o PE, estas janelas estão nos cromossomos 4, 8, 11, 13, 14, 19, 22 e 23, explicando 6,78% da variância total. Com as análises de GWAS foi possível identificar regiões cromossômicas associadas com P16 e PE. A identificação dessas regiões possibilita o melhor entendimento e avaliação destas características, além de indicar genes candidatos para estudos futuros de investigação de...
Keywords: Bovino; Genômica; Melhoramento genetico; Bovino - Reprodução; Genetica animal; Genomics